Triple-decker complexes incorporating three distinct deck architectures. Issue 5 (17th December 2021) - Sun, Xiaofei; Singh, Akhil Kumar; Yadav, Ravi; Jin, Da; Haimerl, Maria; Scheer, Manfred; Roesky, Peter W.
Abstract : Fe–Li–Pb heterotrimetallic triple-decker complexes were synthesized by reduction of pentaphospha- and pentarsaferrocene with the dilithioplumbole. Both complexes comprise bent P5 /As5 middle decks and plumbole as lower decks. Abstract : The reactivity of the dilithioplumbole ([Li2 (thf)2 (μ, η 5 -L Pb )], L Pb = 1, 4-bis- tert -butyl-dimethylsilyl-2, 3-bis-phenyl-plumbolyl) towards the reactive pnictogen precursors P4, pentaphosphaferrocene, and pentaarsaferrocene ([Cp*Fe(η 5 -E5 )] (Cp* = η 5 -C5 Me5, E = P, As)) is reported. The reaction with P4 afforded a phospholyl lithium complex, via lead-phosphorus exchange, while the reactions with [Cp*Fe(η 5 -E5 )] yielded the first examples of Pb–Fe–Li heterotrimetallic triple-decker polypnictogenides with three different deck motifs.